PENDIDIKAN ALTERNATIF BERBASIS OPPORTUNITY WEB (Kritik dan Tawaran Alternatif Ivan Illich dalam Deschooling Society) - Wibowo, Arif (Jurnal Tawadhu, 2018)
During this time almost all levels of society believe that schools are the only educational institutions. Schools seem to be able to uncover great secrets such as ideals, success, prosperity, wealth, or even salvation can only be Pursued through the school path. Though it is all like a assumption-assumptions that hegemony, on the other side of the school just cause social classification causing social problems. Therefore, there must be an alternative education model so that the society is no longer deify and shackled with the model of education in school. Ivan Illich is a theologian and also a radical humanist who criticizes all-out models of education in formal schools. For him the education is universal can not be limited by age, class, or time. Opportunity web is expected to be an alternative education model so that each individual can make the moment learn, share knowledge, and care for each other in every opportunity without limited by space and time. Illich's criticisms and offers are poured into a book called Deschooling Socaity, although it is based on the reality of Latin America and Africa. However, the impact of its development has spread around the world and is still quite pronounced today.                Keywords: Alternative Education, Ivan Illich, Opportunity Web and Deschooling Society